The Role of Relational Embeddedness in Enhancing Absorptive Capacity and Relational Performance of Internationalized SMEs: Evidence From Mainland China - Zhou, Liwen; Chen, Zhong; Peng, Michael Yao-Ping (Frontiers in Psychology, 2022)
The social network in organizational learning process is a critical knowledge source to realize superior performance. This study aims to explore the relationship among relational embeddedness, relational memory and absorptive capacity, and their impact on the relational performance of small and meddle enterprises (SMEs). This study empirically verifies the research framework from 223 Chinese internationalized SMEs. The results confirm previous studies that indicate positive correlations among relational embeddedness, relational memory and absorptive capacity. The results also indicate that relational embeddedness and relational memory have positive effects on relational performance. The findings show that relational memory plays a mediating role in the relationship among relational embeddedness, absorptive capacity and relational performance.